Preliminary studies on extraction of propolis using vitamin E d-ɑ-tocopheryl polyethylene glycol succinate (vitamin E TPGS) and compare their antimicrobial activities - Yee, Tong Kong; Viviana, Abdullah; Siti Umairah, Mokhtar; Rajaletchumy, Veloo Kutty (Malaysian Society for Microbiology, 2020)
Aims: Phenolic compounds with various biological activities such as antimicrobial, anti-inflammatory and antioxidative activity are considered as key compounds in propolis. In this study, propolis was obtained in Kuantan, Pahang and is known to be collected from stingless honey bee Trigona thoracica. The objective of this study is to extract propolis using surfactant vitamin E d-α-Tocopheryl polyethylene glycol 1000 succinate (Vitamin E TPGS) and evaluate its antimicrobial activity compared to water and ethanolic propolis extracts. Methodology and results: Quantitative determinations of phenolic acid and flavonoid such as caffeic acid and quercetin, respectively in propolis extracts were conducted by using High Performance Liquid Chromatography (HPLC). As a result, 70% ethanol extracted propolis (EEP), water extracted propolis (WEP) and 0.02% vitamin E TPGS extracted propolis successfully demonstrate the presence of hydrophilic caffeic acid, while only 70% EEP and 0.02% vitamin E TPGS extracted propolis show the presence of hydrophobic quercetin. Lastly, antimicrobial testing was conducted towards Staphylococcus aureus by using all three different propolis extracts. Conclusion, significance and impact of study: The results showed EEP and vitamin E TPGS propolis extracts exhibit higher antimicrobial activity compared to the WEP.